2013
DOI: 10.5478/msl.2013.4.4.71
|View full text |Cite
|
Sign up to set email alerts
|

Charge-Directed Peptide Backbone Dissociations of o-TEMPO-Bz-C(O)-Peptides

Abstract: In the present study, we report that the charge-directed (assisted) peptide dissociation products, such as b-and y-type peptide backbone fragments, were the major products in MS/MS and MS 3 applications of some o-TEMPO-Bz-C(O)-peptide ions, while radical-driven dissociation products, such as a/x and c/z-type fragments, were previously shown to be the major products in the free radical initiated peptide sequencing mass spectrometry (FRIPS MS). Those o-TEMPO-Bz-C(O)-peptides share a common feature in their seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(34 citation statements)
references
References 31 publications
4
30
0
Order By: Relevance
“…Although this method is somewhat analogous to ECD and ETD, it does not require multiple charges for fragmentation to occur. In fact, the presence of more charges than the number of basic groups can actually inhibit the radical pathways and facilitate charge-induced fragmentation [46]. …”
Section: Introductionmentioning
confidence: 99%
“…Although this method is somewhat analogous to ECD and ETD, it does not require multiple charges for fragmentation to occur. In fact, the presence of more charges than the number of basic groups can actually inhibit the radical pathways and facilitate charge-induced fragmentation [46]. …”
Section: Introductionmentioning
confidence: 99%
“…Similar observations were made for other peptides when the number of charges approached or exceeded the number of basic side chains available, placing an upper limit on the charge states for which CID and PD 266 can produce the desired radical ions. 53 Advantageously, the TEMPO-based FRIPS methodology is also applicable to the study of negative ions. 29 Negative ion mass spectrometry provides structural information for proteomics that is both confirmatory and complementary to that obtained in the study of positive ions.…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…Figure (b) was obtained by providing the normalized collision energy of 15.0 onto singly protonated o ‐TEMPO–Bz(Br)–C(O)–kinetensin, ( R M + H) + . As in the previous FRIPS MS experiments, o ‐TEMPO–Bz(Br)–C(O)–kinetensin ions underwent homolytic dissociation predominantly at the bond between the oxygen of the TEMPO group and the benzylic carbon, producing radical fragment •Bz(Br)–C(O)–kinetensin, ( r M + H) +• , at m/z = 1366.6 . The gas‐phase free energy of the C–O bond homolysis, which generates TEMPO and benzyl radicals, was theoretically predicted to be low at the level of G3(MP2)‐RAD//B3LYP/6‐31G(d), i.e.…”
Section: Resultsmentioning
confidence: 64%
“…electron capture dissociation and ETD, have shown that the radical sites generated through the combination of protonated sites and electrons can induce extensive peptide/protein backbone dissociations . The recognition of the important role played by the radical site in peptide sequencing has triggered the development of a variety of radical‐based MS methods . Collisional activation of ternary metal–peptide–ligand complexes yields peptide radical cations .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation